Background: cigarette smoking is the greatest known risk factor for lung cancer, and people with different smoking status may process risk information differently. While psychological distress has been linked with smoking status, little is known about the (Epidemiology, Biostatistics, and Public Health, 2022)
Background: cigarette smoking is the greatest known risk factor for lung cancer, and people with different smoking status may process risk information differently. While psychological distress has been linked with smoking status, little is known about the impact of distress on lung cancer perception or the moderating role of physical activity and race. This study explores the association of lung cancer perception and distress and investigates the effects of physical activity and race on that association.Methods: the study uses a national, biennial survey (the Health Information National Trends Survey) that was designed to collect nationally representative data on the American public’s need for, access to, and use of cancer-related information using a cross-sectional, complex sample survey design. Out of 5 586 participants, 1 015 were current smokers, 1 599 were former smokers, 2 877 were never smokers. Of the sample, 1 765 participants answered the lung cancer risk perception question and had no personal history of lung cancer. Statistical analysis contrasts smokers, former smokers, and never smokers to examine the association of lung cancer perception and distress and the moderating role of physical activity and race.Results: distress and lung cancer risk perception were significantly positively associated (p value < 0.001). Respondents who were current smokers and were distressed had very high odds of agreeing that they have a somewhat high chance (odds ratio=900.8, CI: 94.23, 8 611.75; p value < 0.001) or a very high chance (odds ratio=500.44 CI: 56.53, 4 430.02, p value < 0.001) of developing lung cancer in the future as compared to not distressed never smokers. However, race and physical activity status did not significantly affect perception of risk. Perceptions of risk are important precursors of health change.Conclusions: elevated distress level and higher perceived risk, in addition to physical activity status and race, could potentially be used to develop targeted interventions, such as tailoring quitting support for smokers at elevated distress levels, which may enhance success rate of quitting smoking and staying quit.